Implementation of the Policy of law Number 25 Of 2009 Concerning Public Services at the Investment and One-Door Integrated Services Service of Belu Regency - Bere, Joseph Franky Leto; Atok, Fransiskus; Buti, Febriani Martins Nai; Buti, Graceana Elma Mau (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The Investment and One-Stop Integrated Service Office of Belu Regency provides public services for residents in Belu Regency to meet their needs in accordance with laws and regulations. In the implementation of services, various obstacles are still encountered, one of which is the low and minimal human resources, both in quality and quantity. The purpose of this study is to describe and analyze the implementation of policies at the DPMPST of Belu Regency. This study uses the Policy Implementation Model proposed by George Edwards III. Policy implementation is examined from four factors, namely: communication, resources, disposition, and bureaucratic structure. The study uses qualitative methods, with data collection techniques through interviews, observation, and documentation. The results of the study indicate that the implementation of the Public Service Mall in Belu Regency has been running in accordance with the provisions of laws and regulations, then to measure the performance of the organizers, a Public Satisfaction Survey was conducted for the period January to June 2025, the quality of service showed very good results with a KIM value of 99.28.